Embrace Fintech in ASEAN: A Perception Through Fintech Adoption Index - Huong, Alice Yong-Zheng; Puah, Chin Hong; Chong, Mei-Teing (Sciedu Press, 2021)
In this new age of financial technology developments in ASEAN, the financial services industry is evolving quickly. However, consumer intention to embrace financial technology in different financial services remains vague. Hence, this study aims to investigate the consumer Fintech adoption level through constructing a Fintech Adoption Index for ASEAN countries. The empirical findings reveal that Singapore with a mature Fintech development having a relatively high adoption rate, while countries with nascent Fintech development such as Brunei Darussalam, Cambodia, Myanmar and Laos have a relatively low adoption rate as compared to the countries with emerging Fintech development such as Indonesia, Malaysia, Philippines, Thailand and Vietnam. All ASEAN countries show increasing trends in Fintech adoption from 2017 to 2019. From this study, the dimensional and final index scores generated are easy to understand, and this study has successfully simplified the complexity of Fintech adoption level across different sub-sectors for all ten ASEAN countries. In conclusion, the newly constructed Fintech adoption index for ASEAN countries can better illuminate consumer adoption preference toward Fintech development and thus leverage the results for productive financial policy direction.